2020
DOI: 10.2478/auoc-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profile and antioxidant activity of bee pollen extracts from different regions of Algeria

Abstract: Due to its complex biochemical properties, the bee pollen is considered one of the functional foods. Bee pollen collected from pollen grains from different botanical sources offers almost a full diet such as carbohydrates, proteins, amino acids, vitamins, minerals. In this study, methanol extracts of 13 honeybee pollen samples were evaluated for flavonoids, phenolic compounds, and antioxidant capacity. Caffeic acid, chlorogenic acid, vanillic acid, p-coumaric acid, gallic acid, quercetin, rutin, vanillin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Studies have shown that 2 mg/ml propolis extract reduces the growth of PAT in apples juices (Silici & Karaman, 2014 ). Propolis is collected by honey bees, making it a rich source of aromatic acids, aromatic esters, volatile compounds, aromatic compounds, hydrocarbons, steroids, flavonoids, acids, micro‐ and macronutrients, vitamins, and essential oils (Hemmami et al., 2020 ; Pobiega et al., 2019 ). The abundance of bioactive compounds present in propolis or cinnamon oil which could reduce the expression of genes involved in PAT biosynthesis (Lai et al., 2021 ) suggests that the composition of herbal blends may also play a role in controlling optimal PAT growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that 2 mg/ml propolis extract reduces the growth of PAT in apples juices (Silici & Karaman, 2014 ). Propolis is collected by honey bees, making it a rich source of aromatic acids, aromatic esters, volatile compounds, aromatic compounds, hydrocarbons, steroids, flavonoids, acids, micro‐ and macronutrients, vitamins, and essential oils (Hemmami et al., 2020 ; Pobiega et al., 2019 ). The abundance of bioactive compounds present in propolis or cinnamon oil which could reduce the expression of genes involved in PAT biosynthesis (Lai et al., 2021 ) suggests that the composition of herbal blends may also play a role in controlling optimal PAT growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[31] Phenolic compounds were extracted using a solvent mixture consisting of ethanol and water. [25] However, alternative solvents like methanol, [32] water, [33] and a combination of water and acetone [34] were also utilized for this purpose.…”
Section: Total Bioactive Compounds Of Mbp Oilsmentioning
confidence: 99%
“…After 3 min, 2 ml of Na2CO3 (20%) solution was added to the mixture. The reaction was held for 30 min in the dark, after which the absorbance was read at λ = 760 nm [26].…”
Section: Determination Of Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…Regular operating standard solutions of phenolic acids are prepared by diluting the stock solution with the mobile step accordingly. Each of these solutions (20 μl) was injected into the column three times and reported peak area and retention periods [26].…”
Section: Preparation Of Standard Solutionmentioning
confidence: 99%